Culture Related Factors May Shape Coping During Pandemics - Shekriladze, Ia; Javakhishvili, Nino; Chkhaidze, Nino (Frontiers in Psychology, 2021)
This study aimed to examine how anxiety related to different styles of coping during the COVID-19 pandemic and how these relationships were moderated by the cultural orientations of individualism/collectivism and a person’s sense of meaning in life. A sample of 849 participants from Georgia completed an online survey during the final stage of lockdown. To measure the main variables, we used the State Anxiety Inventory, the Horizontal and Vertical Individualism and Collectivism Scale, the Meaning of Life Questionnaire, the COVID-19 Worry Scale, and the Ways of Coping Scale tailored to COVID-19 pandemic. The latter measured rational coping via the subscales of information accessing/processing and action-planning coping, and affective coping - via the subscales of passive-submissive and avoidant coping. Results suggested that anxiety positively predicted both affective coping styles and negatively predicted the action-planning coping style, while COVID-19 worry predicted all coping styles; presence of meaning in life positively predicted both rational coping styles and negatively predicted the avoidant coping style, while search for meaning positively predicted all coping styles; individualism negatively predicted the passive-submissive style and positively predicted the action-planning style, whereas collectivism predicted all coping styles; furthermore, individualism and collectivism moderated the link between anxiety and the passive-submissive coping style, presence of meaning in life moderated the link between anxiety and avoidant coping style, while search for meaning in life moderated the link between anxiety and the action-planning coping style. Overall, the findings enrich the cultural transactional theory of stress and coping, and generate insights for the culture-sensitive approach to the meaning in life. The results were conceptualized vis-a-vis Georgia’s intermediate position between clear-cut individualism and clear-cut collectivism.